(untitled) (Bangladesh Journal of Medical Science, 2011)
Although osteosarcoma is the most common primary bone cancer, the incidence in head and neck bony structures is extremely low. As the surgical treatment requires a wide margin excision, the operation usually will be very challenging especially if it involves midline structures. We report a case of a young gentleman who had a bony growth over the epicenter of the hard palate which rapidly occupies the whole oral cavity within 6 months duration. The outline of management is discussed. Keywords: Osteosarcoma; hard palate. DOI: 10.3329/bjms.v10i1.7322 Bangladesh Journal of Medical Science Vol.10 No.1 Jan 2010 pp.57-59